From Bench to Boardroom : the R & D Leader's Guide. - Spiro, Clifford L. (Springer International Publishing, 2017)
References -- 6 Innovation Project Execution -- Stage Gate or Phase Gate Methods -- Five Great Questions for R D Managers to Ask Every Time -- Almost All Projects Fall Behind -- Customer Delays -- Internal Processes Causing Delays -- Pilot Plants -- Overloading and Shifting Prioritization -- Rogue Projects -- Strategic, But Dumb Projects -- Moving Targets and Scope Creep -- Killing Projects -- Success, Rewards, and Recognition -- Summary -- References -- 7: Creating a Culture of Creativity -- Be the Angel's Advocate